Echoes from the Sabine Farm - Horace, 66 BCE-9 BCE; Field, Eugene, 1850-1895; Field, Roswell Martin, 1851-1919 (Salt Lake City, UT : Project Gutenberg, 2004)
"Echoes from the Sabine Farm" by Roswell Martin Field and Eugene Field is a poetic collection published in the late 19th century. This book is a creative reinterpretation of the odes of Horace, reflecting the authors' admiration for the Roman poet's work. The pieces are presented with a blend of humor and lyricism, showcasing themes of nature, love, and the pleasures of life, which resonate with Horace's original themes but also include modern perspectives. The collection comprises various paraphrases and adaptations of Horace's odes, often delivered in a playful and lighthearted manner. The poems explore contemplations of life, love, and camaraderie, set against idyllic pastoral backdrops$1 (Bfrequently invoking the beauty of the Sabine countryside. The voices of the poets convey a deep appreciation for the joys of wine, friendship, and the ephemeral nature of youth, with a vibrant tone that invites readers to relish life's simple pleasures. While echoing the style of classical poetry, these adaptations maintain a conversational quality, making them accessible and enjoyable for contemporary audiences. (This is an automatically generated summary.)s
Release date is 2004-10-27
E-text prepared by Juliet Sutherland, Melissa Er-Raqabi, Leah Moser, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Horace -- Translations into English